2020
DOI: 10.3390/medicina56040178
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Socio-Demographic Factors, Lifestyle and Psychiatric Indicators on Adherence to Treatment of Patients with Rheumatoid Arthritis: A Cross-Sectional Study

Abstract: Background and Objectives: Rheumatoid arthritis (RA) is a severe autoimmune disease characterized by chronic inflammation of the joints accompanied by the progressive deformation and destruction of cartilage and joint bones. This study aims to gain insight into the outcomes related to adherence in patients with rheumatoid arthritis. Predicting the medication adherence in RA patients is a key point to improve the treatment outcome. Materials and Methods: A number of 119 Romanian patients with RA were included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Patients with higher education levels had a higher proportion of medication adherence (p = 0.013), similar to the study by Turcu-Stiolica et al in Rome, from 2017 to 2019 [22]. Many of the results of previous studies demonstrated that people with poor health knowledge tended not to adhere to medication guidelines [23,24].…”
Section: Discussionsupporting
confidence: 84%
“…Patients with higher education levels had a higher proportion of medication adherence (p = 0.013), similar to the study by Turcu-Stiolica et al in Rome, from 2017 to 2019 [22]. Many of the results of previous studies demonstrated that people with poor health knowledge tended not to adhere to medication guidelines [23,24].…”
Section: Discussionsupporting
confidence: 84%
“…In addition, there have been numerous reports of an association between stress and lifestyle [ 5 , 6 , 7 ], and in countries where there is a need to focus on measures for lifestyle-related diseases, it is important to clarify the stress factors that are part of the backdrop to disease.…”
Section: Introductionmentioning
confidence: 99%
“…This result is difficult to compare with the results of studies conducted in other countries in the same group of patients, due to variability of measuring tools and different categorisation of the results regarding the studied variable (two, three or four categories). For instance, in a Brazilian study the level of medication adherence in RA patients was 16.4% [30], in a Dutch study the MA level was 60% [10], and in a Romanian study it was 60.34% for the conventional therapy, and 81.30% for the biological therapy [31].…”
Section: Discussionmentioning
confidence: 99%
“…The number of men and women participating in the study was not equal, but it reflects the dominance of women in the general population of patients with RA. Finally, it should be emphasised that, as demonstrated by other authors [31], medication adherence is a dynamic process, and can change in time, similarly to certain psychological characteristics that may evolve spontaneously, due to life experience, or be changed intentionally, as a result of new competences. Therefore, the results of the study do not necessarily reflect a permanent predisposi-tion for medication adherence in a patient with RA, but rather the present situation, a point in the patient's life.…”
Section: Limitations Of the Studymentioning
confidence: 93%